Alterations in brain white matter contributing to age‐related slowing of task switching performance: The role of radial diffusivity and magnetization transfer ratio. Issue 11 (6th October 2016) - Serbruyns, Leen; Leunissen, Inge; van Ruitenbeek, Peter; Pauwels, Lisa; Caeyenberghs, Karen; Solesio‐Jofre, Elena; Geurts, Monique; Cuypers, Koen; Meesen, Raf L.; Sunaert, Stefan; Leemans, Alexander; Swinnen, Stephan P.
Abstract: Successfully switching between tasks is critical in many daily activities. Age‐related slowing of this switching behavior has been documented extensively, but the underlying neural mechanisms remain unclear. Here, we investigated the contribution of brain white matter changes associated with myelin alterations to age‐related slowing of switching performance. Diffusion tensor imaging derived radial diffusivity (RD) and magnetization transfer imaging derived magnetization transfer ratio (MTR) were selected as myelin sensitive measures. These metrics were studied in relation to mixing cost (i.e., the increase in reaction time during task blocks that require task switching) on a local‐global switching task in young ( n = 24) and older ( n = 22) adults. Results showed that higher age was associated with widespread increases in RD and decreases in MTR, indicative of white matter deterioration, possibly due to demyelination. Older adults also showed a higher mixing cost, implying slowing of switching performance. Finally, mediation analyses demonstrated that decreases in MTR of the bilateral superior corona radiata contributed to the observed slowing of switching performance with increasing age. These findings provide evidence for a role of cortico‐subcortical white matter changes in task switching performance deterioration with healthy aging. Hum Brain Mapp 37:4084–4098, 2016 . ©2016 Wiley Periodicals, Inc .